1993
DOI: 10.1021/bi00214a008
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of active recombinant TIMP-1 from Escherichia coli inclusion bodies and complex formation with the recombinant catalytic domain of PMNL-collagenase

Abstract: TIMP-1 is a member of the family of tissue inhibitors of metalloproteinases involved in regulating the activity of extracellular matrix degrading metalloproteinases. The TIMP-1 cDNA was obtained by reverse transcription-polymerase chain reaction (RT-PCR) amplification of the corresponding mRNA from human fibroblasts. Cloning and expression of the TIMP-1 cDNA were performed in Escherichia coli. In the host vector system chosen, rTIMP-1 is stored intracellularly in its denatured, insoluble form in inclusion bodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Other groups have reported mammalian expression systems for full length and C-terminally truncated forms of TIMP-1 and TIMP-2 [15][16][17] The expression of full-length TIMP-1 in E. coli as inclusion bodies together with procedures for folding and isolation of active protein have been described by others [23][24][25][26]. Although the production of active protein in high yield has been described, Cocuzzi et al [23] reported that their recombinant protein preparations have a high proportion of nonnative molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other groups have reported mammalian expression systems for full length and C-terminally truncated forms of TIMP-1 and TIMP-2 [15][16][17] The expression of full-length TIMP-1 in E. coli as inclusion bodies together with procedures for folding and isolation of active protein have been described by others [23][24][25][26]. Although the production of active protein in high yield has been described, Cocuzzi et al [23] reported that their recombinant protein preparations have a high proportion of nonnative molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Since TIMP-1 does not require glycosylation to be active [21,22], the absence of glycosylation in an E. coli system was not perceived to be problematic. Previous work has shown that mouse TIMP-1 [23] human TIMP-1 [24,25] and human TIMP-2 [26] are expressed as inclusion bodies in E. coli and can be folded in vitro, but the bacterial expression of the aminoterminal domain of TIMP-1 has not been described. Here we describe the expression of the amino-terminal domain of human TIMP-1 (N-TIMP-1) as inclusion bodies, a modified high yield in vitro folding procedure that avoids the production of large volumes of very dilute solutions of protein, and the functional and physical properties of the protein determined by CD spectroscopy and 2D NMR spectroscopy of the l~N-substituted protein.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain biologically active rhTIMP-2, we tried to refold rhTIMP-2 in the conditions used for rhTIMP-1 by Kohono et al [11] in the presence of cystamine, although this procedure was reported as unsuccessful by Kleine et al [13] for rhTIMP-1 and Cocuzzi et al [12] for mouse TIMP-1. Kohono's procedure also failed to produce active human rTIMP-2 from E. coli (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…This was because TIMP-2 contains 12 cysteine residues which have the potential to originate numerous disulphide bridges, and at high protein concentrations both intra-and inter-chain bonds may take place: in both cases, incorrect disulphide bonds may result. To avoid this problem, during refolding the protein must be diluted below 20 ¢tg/ml, thus avoiding aggregation, precipitation and loss of activity [13]. Nevertheless, because of the intrinsic chemical-physical characteristics of each protein, satisfactory activity yield is not routinely achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation